2016
DOI: 10.4103/0973-1296.182164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of procyanidin-rich extract from natural cocoa powder on cellular viability, cell cycle progression, and chemoresistance in human epithelial ovarian carcinoma cell lines

Abstract: Background:Over the last 400 years, cocoa and chocolate have been described as having potential medicinal value, being consumed as a beverage or eaten as food. Concentration–dependant, antiproliferation, and cytotoxic effects of some of their polyphenolic constituents have been demonstrated against various cancers. Such an effect remains to be demonstrated in ovarian cancerObjective:To investigate the effect of cocoa procyanidins against ovarian cancer in vitro using OAW42 and OVCAR3 cell lines.Materials and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Polyphenol structure is characterized by the presence of multiphenol units, which might contribute to oxidative stability of plant tissue and other organoleptic characteristics, such as color, flavor, and odor ( Pandey and Rizvi, 2009 ). Due to favorable safety profile and profound antioxidant activity, polyphenolic phytochemicals have been intensively studied as anticancer adjuvants ( Lai et al, 2017 , Akowuah et al, 2009 , Taparia and Khanna, 2016 ). Particularly, in mice‑harboring mammary carcinoma 4T1, green tea polyphenols dramatically suppressed cancer development and inhibited tumor metastasis ( Baliga et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenol structure is characterized by the presence of multiphenol units, which might contribute to oxidative stability of plant tissue and other organoleptic characteristics, such as color, flavor, and odor ( Pandey and Rizvi, 2009 ). Due to favorable safety profile and profound antioxidant activity, polyphenolic phytochemicals have been intensively studied as anticancer adjuvants ( Lai et al, 2017 , Akowuah et al, 2009 , Taparia and Khanna, 2016 ). Particularly, in mice‑harboring mammary carcinoma 4T1, green tea polyphenols dramatically suppressed cancer development and inhibited tumor metastasis ( Baliga et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Procyanidin treatment increased the G1 cell population in BxPC-3 ( 45 ), OVCAR ( 46 ), oral squamous cell carcinoma 25 (SCC-25) ( 11 ), and Caco-2 cells ( 23 ), which is demonstrative of its apoptotic effects. Earlier studies suggest that the procyanidin-induced arrest of the cell cycle might be mediated by the induction of p21 expression ( 19 , 47 ).…”
Section: Chemopreventive Potential Of Procyanidinmentioning
confidence: 98%
“…Taparia et al . ( 46 ) reported that procyanidin is cytotoxic to QAW42 and OVCAR3 epithelial ovarian cancer cells via several mechanisms, inducing apoptosis with DNA damage and caspase-3 mediation. Downregulation of pro-MMP-2 and reduction in active MMP-2 levels imply a decreased invasive potential of the cells ( 51 ).…”
Section: Chemopreventive Potential Of Procyanidinmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] Due to favorable safety profile and profound antioxidant activity, polyphenolic phytochemicals have been intensively studied as anticancer adjuvants. [ 8 9 10 ] Particularly, in mice-harboring mammary carcinoma 4T1, green tea polyphenols dramatically suppressed cancer development and inhibited tumor metastasis. [ 11 ] Furthermore, a clinical study on patients with intestinal premalignant lesions showed that 6-month treatment of quercetin and curcumin inhibited the development of polyps both in number and size.…”
Section: Introductionmentioning
confidence: 99%